Early development of Cymatium (Monoplex) pileare and C. (Linatella) cutaceum (Ranellidae : Gastropoda : Mollusca) in the laboratory - Muthiah, P; Sampath, K (Indian Journal of Fisheries, 2011)
Early development of two species of ranellids, Cymatium (Monoplex) pileare andC. (Linatella) cutaceum were studied in the laboratory. Females incubated theegg mass for 12-25 days till fully developed larvae were hatched out through anapical orifice of the egg capsule. The mean length and height of the released larvaeof C.(M.) pileare and C.(L.) cutaceum were 252 and 166 pm and 265 and 191pmrespectively. The percentage of hatching and larval development was 95.6 and100 for CAM.)pileare and 93.7 and 94.6 for C.(L.) cutaceum respectively. The larvaldevelopment inside the egg capsule of these species are discussed.